Eyes to see Goya (Journal of Parents and Teachers, 1996)
Francisco de Goya, a member of the Royal Academy of San Fernando, suffered from deafness and created iconic works such as “Los Caprichos” and portraits of the royal family. In 1814, the Inquisition censored his works “La maja vestida” and “La maja desnuda”, which led him to exile in Bordeaux, where he died in 1828. His legacy includes more than 700 works, including 124 in the Prado Museum.
Keywords: deafness; iconic works; inquisition; exile